Strategi Dakwah Inklusif Terhadap Jama’ah Tabligh Tunarungu di Masjid Raya At-Taqwa Kota Mataram - siwestin, siwestin (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2025)
The implementation of da'wah in mosques in general is still oriented towards normative worshippers so as to set aside people with deaf disabilities. The inability of the da'i to use sign language has caused this group to be marginalized from optimal access to Islamic teachings, even though the number of deaf people in Indonesia continues to increase and their spiritual needs are as great as other worshippers. This study aims to explore inclusive da'wah strategies for deaf worshippers at the At-Taqwa Mataram Grand Mosque through a descriptive qualitative approach with non-participatory observation data collection techniques, in-depth interviews, and documentation. The results of the study show that the provision of sign language interpreters, the use of cellphones for visual communication, and the implementation of special mudzakarah forums for the deaf have succeeded in increasing the understanding of Islamic teachings, the intensity of worship, and the active participation of deaf worshippers in the study. These findings prove that inclusive da'wah not only fulfills the religious rights of people with disabilities, but also strengthens the essence of mosques as a welcoming institution that embraces all levels of people. Keywords: Inclusive Da'wah, Deaf, Sign Language, Inclusive Mosque, Tabligh Congregation.